Deníky Marie Jany hraběnky Harbuval von Chamaré (1722-1792) - Pavla Janáčková (Theatrum Historiae)
Diaries of aristocratic women who lived in the Bohemian kingdom in the 18th century are rather rare. Three diaries of Maria Johanna Harbuval von Chamaré (from years 1769-1773, 1782 and 1791) and five diaries of her mother-in-law Anna Barbora Harbuval von Chamaré (from years 1763-1771) are the oldest ones preserved for the Bohemian kingdom. The authoress tries to describe everyday life of Maria Johanna Harbuval von Chamaré (1722-1792) using this unique ego-documents and compare it with other kinds of resources connected with her life (correspondence, inventories, accounts, testament, etc.). She intents to resume all themes which Maria Johanna was writing in her diaries and private corre- spondence about. Among the most important points of her interest belonged her relationship with her husband Johann Anton Harbuval von Chamaré who is known for his unusual hobbies (for example searching for treasure under the old castle in Potštejn), relationship with other persons of noble origin and reflection of political events of the 18th century. Her everyday notes also inform us about her everyday activities, such as care about household and representation, accountig, travelling, typical aristocratic seasonal entertainmet (going out to theatres, balls, hunting, etc.) and everyday entertainment (visiting other noble persons, playing billiard, card games, chess, etc.). She did not spend every day being in a noble company, she was very often alone passing time with writing letters or knitting. The authoress also mentions her serious health troubles that often disabled her for taking part in many of above mentioned actvities. Finally, she summarizes that Maria Johanna was an inte- resting personality and the example of a noble woman who was married but did not give birth to any child. Her diaries show us what a life could such a woman live. On the other hand, she might have done many other things in her lifetime. Some of other aristocratic women became meacenases, enjoyed being in company all the time, meeting other noble women. However, Maria Johanna probably prefered a quiet way of living, but it is also possible that the lack of other archive material disallows us to reveal all her life. We must not forget that her personal diaries reflect only its shorter part.